Percutaneous methods of left atrial appendage exclusion: an alternative to the internist - Duong L. Le; Soidjon D. Khodjaev; Remo L. Morelli (Greater Baltimore Medical Center, 2014)
Thromboembolic stroke from the left atrial appendage (LAA) is the most feared complication in patients with atrial fibrillation (AF). The cornerstone for the management of chronic non-valvular AF is stroke reduction with oral anticoagulation (OAC). However, poor compliance, maintaining a narrow therapeutic window, and major side effects such as bleeding have severely limited their use, which creates a therapeutic dilemma. As much as 20% of AF patients are not receiving OAC due to contraindications and less than half of AF patients are not on OAC due to reluctance of the prescribing physician and/or patient non-compliance. Fortunately, over the past decade, there have been great interests in providing an alternative strategy unbeknownst to the practicing internist. The introduction of percutaneous approaches for LAA occlusion has added a different dimension to the management of chronic AF in patients with OAC intolerance. Occlusion devices such as the Amplatzer Cardiac Plug and WATCHMAN device are currently being investigated for stroke prophylaxis. More recently, the LARIAT device may provide an alternative means for potential stroke prophylaxis without the need for short-term post-procedural OAC. We aim to review the current literature and bring attention to an alternative strategy for high-risk AF patients intolerant to OAC.